1993
DOI: 10.1002/cne.903370102
|View full text |Cite
|
Sign up to set email alerts
|

The organization of projections from the mediodorsal nucleus of the thalamus to orbital and medial prefrontal cortex in macaque monkeys

Abstract: The organization of interconnections between the mediodorsal nucleus of the thalamus (MD) and the orbital and medial prefrontal cortex and the agranular insular cortex in the monkey was studied by retrograde and anterograde tracing techniques. In addition to the magnocellular and parvicellular divisions of MD, three other subdivisions can be recognized on the basis of myeloarchitecture, cytoarchitecture, and connections. The first two of these represent a parcellation of the magnocellular division into a later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
276
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(303 citation statements)
references
References 74 publications
26
276
0
Order By: Relevance
“…Ipsilateral side dominant limbic structures were involved in the epileptic excitation in the present model, probably based on the neuronal connections between limbic structures, mainly in the basolateral nucleus of the amygdala, and the magnocellular division of the MD. 21) In the present study, SWDs were continuously observed at about 2.5 Hz for 5-7 hours after kainic acid injection to the unilateral MD in rats, and epileptiform activity propagated to the cortex and thalamic nucleus, and to the limbic system. These discharges were synchronized in the bilateral MDs.…”
supporting
confidence: 52%
“…Ipsilateral side dominant limbic structures were involved in the epileptic excitation in the present model, probably based on the neuronal connections between limbic structures, mainly in the basolateral nucleus of the amygdala, and the magnocellular division of the MD. 21) In the present study, SWDs were continuously observed at about 2.5 Hz for 5-7 hours after kainic acid injection to the unilateral MD in rats, and epileptiform activity propagated to the cortex and thalamic nucleus, and to the limbic system. These discharges were synchronized in the bilateral MDs.…”
supporting
confidence: 52%
“…1; Ray and Price 1993). This arrangement is notable, as removal of the medial and orbital prefrontal cortices induces severe DNMS deficits in monkeys (Fig.…”
Section: Nonhuman Primatesmentioning
confidence: 83%
“…The ventral CG (BA 25) is implicated in mediating the emotional responses to salient stimuli (rewarding as well as aversive) (Elliott et al, 2000) and imaging studies have shown that BA 25 is activated by natural and drug rewards (Breiter et al, 1997, Francis et al, 1999Berns et al, 2001). Thus the negative association between D2 receptors and the tendency to eat when exposed to negative emotions we previously reported in healthy controls (Volkow et al, 2003) could be mediated by modulation of BA 25.The association between metabolic activity in prefrontal regions and D2 receptors could reflect projections to the prefrontal cortex from ventral and dorsal striatum (Ray and Price, 1993), which are regions implicated in the reinforcing and motivational effects of food (Koob and Bloom, 1988) and/or from the ventral tegmental area (VTA) and substantia nigra (SN), which are the main DA projections to striatum (Oades and Halliday, 1987). However, the prefrontal cortex also sends projections to the striatum so the association could reflect the prefrontal regulation of DA striatal activity (Murase et al, 1993).…”
mentioning
confidence: 73%
“…The association between metabolic activity in prefrontal regions and D2 receptors could reflect projections to the prefrontal cortex from ventral and dorsal striatum (Ray and Price, 1993), which are regions implicated in the reinforcing and motivational effects of food (Koob and Bloom, 1988) and/or from the ventral tegmental area (VTA) and substantia nigra (SN), which are the main DA projections to striatum (Oades and Halliday, 1987). However, the prefrontal cortex also sends projections to the striatum so the association could reflect the prefrontal regulation of DA striatal activity (Murase et al, 1993).…”
Section: Association Between D2 Receptors and Prefrontal Metabolismmentioning
confidence: 99%